Peliosanthes luteoviridis (Asparagaceae), a new species with yellowish green flowers from southern Vietnam - Vislobokov, Nikolay A.; Romanov, Mikhail S.; Nguyen, Khang Sinh; Pham, van The; Dat Pham, Thi Thanh; Nguyen, van Canh; Тanaka, Noriyuki; Kalyuzhny, Sergey S.; Kuznetsova, Svetlana P.; Kuznetsov, Andrey N.; Nuraliev, Maxim S. (Phytotaxa, 2022)
Peliosanthes luteoviridis is described and illustrated as a new species from southern Vietnam (Dong Nai Province, Cat Tien National Park). It is most similar to P. macrostegia in having stamens forming a hemispheric corona and a pistil somewhat abruptly narrowing to a conoid style, but differs mainly in dense inflorescence, terete peduncle, entirely yellowish green flowers and somewhat thin-textured translucent perigone.